MEDIA ARCHIVE: A NEW STEP TOWARDS PRESERVING NATIONAL DIGITAL HERITAGE (Bulletin of Armenian Libraries, 2025)
The National Library of Armenia (NLA) has launched Media Archive, a pioneering digital platform designed to collect and preserve online media content as part of Armenia’s national heritage. Developed by a young professional of Université Française en Arménie (UFAR), the system automates the collection of content from Armenian news websites, capturing articles, blogs, and other born-digital materials that are at risk of disappearing. The platform addresses a critical gap in Armenia’s legal deposit system, which currently applies mostly to printed materials.Using web scraping technologies, data is collected, cleaned, and archived with metadata, ensuring long-term access and legal authenticity. A user-friendly interface enables librarians to manage and search the archive effectively. Future enhancements include OCR integration for digitized historical materials and catalog system integration.Media Archive establishes the technological foundation for an electronic legal deposit system and reflects NLA’s commitment to safeguarding Armenia’s digital cultural memory for future generations and supporting scientific research and cultural preservation.